KAJIAN LITERATUR : IMPLEMENTASI MODEL PROBLEM BASED LEARNING MUATAN SAINS SEKOLAH DASAR DI ERA REVOLUSI 5.0 - Wiwin Kusrianto, Wiwin (Pedagogik : Jurnal Pendidikan Guru Sekolah Dasar, 2025)
In the 21st century and the era of Society 5.0, 4C skills in Critical Thinking and Problem Solving, Creativity, Communication Skills, and Collaboration Skills are crucial for students. However, the level of these skills remains low, particularly in Science Education. This study aims to evaluate the implementation of the Problem-Based Learning (PBL) model in Science Education to enhance students' 4C skills. Utilizing a descriptive qualitative approach with literature studies, data were collected from journal articles in the Google Scholar database and analyzed documentarily. The results indicate that PBL is effective in improving students' critical thinking, creativity, collaboration, and communication skills, as well as preparing them to face the challenges of an increasingly automated workforce. This research also highlights the importance of active learning that facilitates students' interaction with knowledge, making them more prepared to adapt to changing times. Additionally, this study provides insights into the role of teachers as facilitators, enabling students to learn independently. By adopting PBL, schools can create a dynamic and responsive learning environment, equipping students with practical skills that are essential for the future.